Merah Darah Hijau Tanaman: Tragedi Sistem Tanam Paksa dan Awal Runtuhnya Hindia Belanda - Safitri, Via Dwi Ria Dwi Ria (Maliki Interdisciplinary Journal, 2024)
The implementation of the Cultivation System (Cultuurstelsel) in 1830 by Governor- General Johannes van den Bosch marked a dark chapter in the history of the Dutch East Indies. While the system aimed to boost the colonial economy through export crops like coffee, tea, and sugarcane, it resulted in immense suffering and exploitation of the Indonesian people. Lands were seized, labor was forced, and crops were confiscated, leading to widespread resistance and resentment. The Cultivation System's brutality and injustice sparked criticism from both liberals and humanists, both within and outside the Dutch East Indies. Liberals condemned it as a violation of free-market principles, while humanists decried its inhumane and exploitative nature. These criticisms fueled the anti-colonial movement and contributed to the eventual downfall of the Dutch East Indies. While factors like World War I, Indonesian nationalism, and the global economic crisis also played a role, the Cultivation System served as a catalyst for various upheavals, including the Diponegoro War, the Aceh War, the Batak War, and the rise of anti-colonial movements.